Implementasi Manajemen Kurikulum Pesantren di Ponpes Al Urwatul Wutsqo Diwek Jombang - Nurul Indana; Leni Nurvita (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
Islamic boarding schools are traditional Islamic educational institutions to study, understand, explore, live, and practice Islamic teachings by emphasizing the importance of religious morals as guidelines for daily behavior. Curriculum management is important, to make the mission and vision of the boarding school targets in accordance with the boarding school objectives based on the level and necessary. Curriculum management includes planning, implementing, and evaluating curriculum activities. The curriculum management of Al Urwatul Wutsqo Islamic boarding school, is al Qur'an-based (Qur'an and Interpretation Development). This study is a qualitative research method, with data collection using interviews, observation and documentation and triangulation as an anlysis. The results of the study are conducting deliberations and coaching with the boarding school caretakers and all religious teachers / clerics (planning), the implementation is the activity of qur'any learning and tafsir amaly, and in evaluation is the responsible report to ustadz/ustadzah about the results, supporting factors: the curriculum has made can be followed since all teachers are the alumni of the Islamic boarding school Al Urwatul Wutsqo, and the inhibiting factor is the bussines of the teacher ho are studying, so that their time is disturbed.